2015
DOI: 10.1108/el-03-2014-0051
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Twitter on libraries: a critical review of the literature

Abstract: Purpose – The paper aims to present a critical review on the adoption and use of Twitter in libraries. Twitter, a microblogging service, is becoming more and more popular among libraries as a means of reaching users and as a marketing tool for their services. Design/methodology/approach – The method of systematic review is used to identify, collect and critically present all relevant literature. Papers’ aims were analyzed to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Twitter also contributes to libraries being more engaged, productive and building relationships. Research by Vassilakaki and Garoufallou (2015) found that 77.8% cent of the libraries used Twitter for work purposes. Huang et al (2017) discussed that libraries also use Twitter to create and promote a sense of community among libraries and users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twitter also contributes to libraries being more engaged, productive and building relationships. Research by Vassilakaki and Garoufallou (2015) found that 77.8% cent of the libraries used Twitter for work purposes. Huang et al (2017) discussed that libraries also use Twitter to create and promote a sense of community among libraries and users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies explored the implementation of social media tools, including Twitter, by libraries in various contexts (i.e. public libraries, academic libraries and academic institutions) and from various angles, including why and how libraries use social media [1620], the impact of social media [21], identifying connecting users [22,23] and social media policies and guidelines [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, librarians of this age have a need to adopt new roles and technologies to match user's expectations for new modes of communication and access to information (Vassilakaki & Garoufallou, 2015). But Johnson (2012a) found that most librarians do not feel at home in using emerging modern technologies and prefer using traditional methods.…”
Section: Survey Of Literaturementioning
confidence: 99%